ANALISIS KONDISI DAN DISTRIBUSI POTENSI EKONOMI DI KABUPATEN SUMBAWA BARAT - Martina Ayu Sejati; Poppy Haryani; Tugma Jaya Manalu; Arfita rahmawati; Febriyanti Angelia Ginting (Jurnal Geografi, 2025)
An important aspect in describing the success of development is through analyzing the economic conditions of the region. Economic analysis also plays an important role in assessing regional inequality. Kabupaten Sumbawa Barat is one of the regions that has a diversity of resources and has various types of economic sectors. The objectives of this research include: (1) Analyzing the regional financial capacity in Kabupaten Sumbawa Barat; (2) Analyzing the Economic Base Sector by business field in Kabupaten Sumbawa Barat in 2019-2023; and (3) Analyzing the value of Economic inequality in Kabupaten Sumbawa Barat. The method applied in this research is quantitative descriptive method with secondary data from the Central Bureau of Statistics, and related agencies. The calculation techniques used are: Calculation of regional financial capability (Degree of Fiscal Decentralization); Financial Independence (Degree of Fiscal Autonomy); Location Quotient (LQ); and Williamson Index. The results showed that the value of the Degree of Fiscal Decentralization (DDF) in Kabupaten Sumbawa Barat in 2019 was 6% and fell into the category of very less, while for 2020 to 2023 it was 13% and fell into the category of less. Meanwhile, the value of the Degree of Fiscal Autonomy (DOF) in 2019 is the lowest value, namely 11.3 and has increased in 2023 to 22 and is included in the concurrency classification. The base sector is the mining and quarrying sector (4.78). The other three sectors that have the highest value and potential are the transportation and storage sector (0.31), the construction sector (0.29) and the agriculture, forestry and fisheries sector (0.29).While the sector with the lowest value is the processing industry (0.07). The value of economic inequality using the Wiliamson Index shows an inequality value of 0.77 and falls into the high inequality category.